The role of special schools in providing services and fulfilling the right to education for children with special needs - Fauzian, Mochammad Fiqry; Kania, Delila; Elan, Elan (ARKA INSTITUTE, 2023)
The role of special schools in serving and fulfilling the right to education for children with special needs is very important. special schools provide PKPBI (Development of Communication Perception Sound and Rhythm) learning materials for children with special needs. This study aims to determine the planning, constraints, and ways to overcome obstacles to the role of special schools in serving the fulfillment of the right to education for children with special needs at SLB-B Tut Wuri Handayani Bandung City. This research approach uses a qualitative research approach with a case study research method. Data collection interviews, observation and documentation. In this study, the research subjects were the principal, teachers, administration, and students with special needs. The results showed that the role of special schools in serving and fulfilling the right to education for children with special needs has been well fulfilled. Children with special needs as students also get their rights fulfilled, grants from the government that have been registered in Dapodik (Basic Education Data). Obstacles to children with special needs as students cannot get financial assistance from the government because the documents in Dapodik are incomplete. The way to overcome this is to remind parents to collect complete documents.